Immunotherapy for Cutaneous Squamous Cell Carcinoma: Results and Perspectives - Alberti, Andrea; Bossi, Paolo (Frontiers in Oncology, 2022)
Although initial surgical excision cures 95% of patients, a minority of cutaneous squamous cell carcinomas (cSCCs) are unresectable, either locally advanced or with unresectable regional lymph nodes or distant metastases. These patients are offered systemic treatments. Response rate to chemotherapy is relatively low and not durable, as well as the results obtained with epidermal growth factor inhibitors (EGFRi). Like others cutaneous tumors, cSCC have high immunogenicity, driven by the high mutational burden, the ultraviolet signature and the over-expressed tumor antigens. Two checkpoint inhibitors, cemiplimab and pembrolizumab, achieved high response rate and survival with less toxicities than other available systemic agents. These promising results prompted to investigate new combination strategies of systemic therapy and surgery or radiotherapy. Subgroup analysis showed promising role of immunotherapy to facilitate surgery in locally advanced cSCC and, in a small group of patients, long term survivals without resection. However, some cSCCs treated with immunotherapy develop either early or late resistance, so new drugs and new combinations are in clinical study to overcome the mechanism underpinning these resistances. The present review focuses on the progress with immunotherapy to date and on new therapeutic strategies for cSCC.